2015
DOI: 10.4103/2321-1407.163418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various anthropometric proportions in Indian beautiful faces: A photographic study

Abstract: Introduction The subject of beauty has been the topic of much debate throughout history, and methods for the evaluation of beauty have been the focus of many research projects. The evaluation of beauty is influenced by factors which include various linear measurements, angles, ratios, and proportions. We evaluated several ratios in Indian Population after locating various landmarks on beautiful Indian faces. Aims and Objectives The aim of the present study was to evaluate various facial proportions of Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
5
11
0
Order By: Relevance
“…In the present study, the means of mandibulo lower face height index (0.67) and upper face to face height index (0.63) were close to the golden proportions which are similar to the previous studies on Indian women (0.65; 0.69) (Kalra et al, 2015) and Caucasian women (0.61; 0.69) (Farkas, 1994) respectively. In horizontal to horizontal facial ratios on Indian American women, mouth face width index was similar with previous studies done on Indian women (Kalra et al, 2015;Jagadish Chandra et al, 2012;Farkas, 1994) and North American White women (Farkas and Cheung, 1979). The mandibular face width (Jagadish Chandra et al, 2012) and intercanthal nasal width (Kalra et al, 2015;Jagadish Chandra et al, 2012) indices in Indian women studies were also similar with present study whereas, North American White women (Farkas and Cheung, 1979) and Indian women (Farkas, 1994) studies showed statistically significant difference (p<0.001).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In the present study, the means of mandibulo lower face height index (0.67) and upper face to face height index (0.63) were close to the golden proportions which are similar to the previous studies on Indian women (0.65; 0.69) (Kalra et al, 2015) and Caucasian women (0.61; 0.69) (Farkas, 1994) respectively. In horizontal to horizontal facial ratios on Indian American women, mouth face width index was similar with previous studies done on Indian women (Kalra et al, 2015;Jagadish Chandra et al, 2012;Farkas, 1994) and North American White women (Farkas and Cheung, 1979). The mandibular face width (Jagadish Chandra et al, 2012) and intercanthal nasal width (Kalra et al, 2015;Jagadish Chandra et al, 2012) indices in Indian women studies were also similar with present study whereas, North American White women (Farkas and Cheung, 1979) and Indian women (Farkas, 1994) studies showed statistically significant difference (p<0.001).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, vertical to vertical facial ratios on Indian American women, mandibulo lower facial height, nose-facial height, mandibulofacial height, upper lip upper face height, upper lip nose height and upper lip mandible height indices were similar with previous studies done on Indian women (Kalra et al, 2015;Jagadish Chandra et al, 2012;Farkas, 1994) and North American White women (Farkas and Cheung, 1979). The lower face-face height (Kalra et al, 2015;Jagadish Chandra et al, 2012) mandibulo upper facial height (Kalra et al, 2015) and upper faceface height (Kalra et al, 2015;Farkas, 1994) indices in Indian women studies were also in agreement with present study whereas, North American White women (Farkas and Cheung, 1979) study showed statistically significant difference (p<0.001). In the available literature search, I could not find the data on ear lower face index, ear nose height index and nose lower face height index for the comparison.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations